1995
DOI: 10.1111/j.1365-4362.1995.tb04380.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Port‐wine Stains

Abstract: Although some differences exist, acquired port-wine stains are similar to congenital port-wine stains in their clinical morphology, histologic findings, and response to laser treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 16 publications
1
33
0
1
Order By: Relevance
“…But in these articles, only small numbers of patients were studied and the therapeutic results were not same in all patients with APWS. As for our experience of long pulsed dye laser in APWS therapy, the result was rather similar to that of Dinehart et al 1 . The response to PDL in patients with APWS was controversial, so we undertook this study to find out whether there are some differences of histopathologic features of the two entities or not.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…But in these articles, only small numbers of patients were studied and the therapeutic results were not same in all patients with APWS. As for our experience of long pulsed dye laser in APWS therapy, the result was rather similar to that of Dinehart et al 1 . The response to PDL in patients with APWS was controversial, so we undertook this study to find out whether there are some differences of histopathologic features of the two entities or not.…”
Section: Discussionsupporting
confidence: 77%
“…Many cases of acquired PWS have since been reported [1][2][3]5,18 but there has been little discussion about treatment 1,2 . There have been only two reports investigating the efficacy of laser therapy in APWS 1,2 . Dinehart et al 1 found that APWS had generally a faster response to the PDL treatment than CPWS, however, they could not explain the exact mechanism because some patients responded rather poorly to laser treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations